Validation of MALDI-TOF MS Biotyper database optimized for anaerobic bacteria: The ENRIA project. (December 2018) - Veloo, A.C.M.; Jean-Pierre, H.; Justesen, U.S.; Morris, T.; Urban, E.; Wybo, I.; Kostrzewa, M.; Friedrich, A.W.; ,
Abstract: Within the ENRIA project, several 'expertise laboratories' collaborated in order to optimize the identification of clinical anaerobic isolates by using a widely available platform, the Biotyper Matrix Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS). Main Spectral Profiles (MSPs) of well characterized anaerobic strains were added to one of the latest updates of the Biotyper database db6903; (V6 database) for common use. MSPs of anaerobic strains nominated for addition to the Biotyper database are included in this validation. In this study, we validated the optimized database (db5989 [V5 database] + ENRIA MSPs) using 6309 anaerobic isolates. Using the V5 database 71.1% of the isolates could be identified with high confidence, 16.9% with low confidence and 12.0% could not be identified. Including the MSPs added to the V6 database and all MSPs created within the ENRIA project, the amount of strains identified with high confidence increased to 74.8% and 79.2%, respectively. Strains that could not be identified using MALDI-TOF MS decreased to 10.4% and 7.3%, respectively. The observed increase in high confidence identifications differed per genus. For Bilophila wadsworthia, Prevotella spp., gram-positive anaerobic cocci and other less commonly encountered species more strains were identified with higher confidence. A subset of the non-identified strains (42.1%) were identified using 16S rDNA gene sequencing. The obtained identities demonstrated that strains could not be identified either due to the generation of spectra of insufficient quality or due to the fact that no MSP of the encountered species was present in the database. Undoubtedly, the ENRIA project has successfully increased the number of anaerobic isolates that can be identified with high confidence. We therefore recommend further expansion of the database to include less frequently isolated species as this would also allow us to gain valuable insight into the clinical relevance of these less common anaerobic bacteria. Highlights: European Network for the Rapid Identification of Anaerobes (ENRIA). Validation of a for anaerobic bacteria optimized MALDI-TOF MS database. The increase in high confidence identification differed per genus. Further expansion of the database for the identification of less common species is recommended.